(untitled) (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2021)
Originally practical use of fractional differential operators in transmission line analysis of electrical systems is made by Oliver Heaviside in 1890, after Guillaume de l’Hôpital first proposed the concept of fractional calculus. The lack of a physical understanding of FC made it unpopular among engineers and scientists. Derivatives and integrals of the fractional order (FO) do not have the same properties as those of the integer-order derivatives or integrals. However, because of this, they can be generalized (fractional or non-integer order) An unstable pendulum system on a cart was used in this thesis, and controlling such systems can be a bit of a challenge. Heavy loads are often transported using a 2-D Gantry crane system, which is controlled by workers manually and often attained at the user’s ability level to transport and may lead to serious mishaps. We provide in this thesis a new approach for improving FO models of systems in order to develop controllers without using hitand-trial methods that yield fractional models. Results from this technique are compared to previous fractionalorder models. For these existing models, we propose a new fractional-order model that enhances performance by a factor of two.